Investigation of A New Local Isolate of Penicillium Lanosocoeruleum That Produces The Antifungal Griseofulvin - Mohammed Yahya Ali Allawi, Warka Saeed Qassim Al-Taee, (Pakistan Journal of Medical & Health Sciences, 2022)
Penicillium (140) isolates were isolated from different sources to investigate penicillium species that produced griseofulvin. Penicillium species were identified according to taxonomic keys. P.lanosocoeruleum was isolated from wheat grains that produce the extrolites, tryptoquialanins, griseofulvin, and viridicatumtoxin. P.lanosocoeruleum have been also diagnosed molecularly by detection of the presence of the Internal Transcribed Spacer )ITS( in fungi using PCR technique. After the fungus was diagnosed, recorded in the NCBI as a new isolate LC635342.1. Several methods have been used to detect the production of the antifungal griseofulvin of P.lanosocoeruleum, Potassium dichromate detection, dichloromethane detection, extraction of griseofulvin industrially, and bioactivity test against dermatophytes fungi (Trichophyton mentagrophytes).